Functional Intestinal Obstruction of Prematurity (FIOP): Short term management results: A case series - Daniel Acosta Farina; Verónica Polit-Guerrero; Johan Aguayo-Vistin; Cristhian Cedeño-Moreira; Vicente Salinas-Salinas; Daniel Acosta-Bowen; jorge Oliveros-Rivero (EL-Med-Pub, 2022)
Background: Functional Intestinal Obstruction of Prematurity (FIOP) is the delay or failure of meconium evacuation in premature neonates. It is associated with hypomotility in the developing intestine. It mostly presents with signs of intestinal obstruction in very low (VLBW) or extremely low birth weight (ELBW) neonates. Case Series: We present short-term results regarding the management of 8 premature newborns with FIOP treated with Awolaran O. et al [1] algorithm in a pediatric hospital, two of them required a surgical procedure due to conservative management failure. Conclusion: Early conservative management is successful in most patients with FIOP, related to symptom resolution. Surgical management should be kept for those with conservative management failure.